Perinatal Palliative Care Service: Developing a Comprehensive Care Package for Vulnerable Babies with Life Limiting Fetal Conditions. Issue 4 (October 2022) - Tewani, Komal G.; Jayagobi, Pooja A.; Chandran, Suresh; Anand, Amudha J.; Thia, Edwin W. H.; Bhatia, Anju; Bujal, Rahimah; Khoo, Poh Choo; Quek, Bin Huey; Tagore, Shephali; Chua, Mei Chien
Background: Perinatal Palliative Care provides comprehensive and holistic care for expectant and new parents, who receive a diagnosis of life-limiting fetal condition and opt to continue pregnancy and care for their newborn infant.Aim: To develop a service providing individually tailored holistic care during pregnancy, birth, postnatal and bereavement period.Methods: Following a baseline survey of neonatologists and discussions with key stakeholders we launched the Perinatal Palliative service at the KK Women's and Children's hospital, Singapore in January 2017. The multidisciplinary team, led by a Palliative care specialist comprised of Obstetricians, Neonatologists, nurses and medical social workers. The Birth defect clinic referred parents with antenatally diagnosed 'Lethal' fetal conditions. The team checked the understanding and the decision making process of parents and initiated and finalized advance care plans. The service also embraced deserving postnatal referrals upon request.Results: A total of 41 cases were seen from January 2017 to December 2019. Of these, 26/41(63%) were referred antenatally and had completed advance care plans. 18/41 (44%) died during or shortly after birth and 10/41(24%) continue to survive and are supported by the community palliative team. During this time a workflow was formulated and modified based on parent and team feedback.Conclusion: Awareness of the service has increased over the years and a clear workflow has been formulated. Advance care plans are prepared and documented before birth so as to enable service teams on board to provide well timed pertinent care. Feedbacks from parents about this service were positive.